Analysis of Factors Influencing the Decision of Couples of Childbearing Age to Participate in the Family Planning (KB) Program in Purwakarta Regency, Indonesia - Khalifah, Intan Noor (HM Publisher, 2024)
Introduction: The family planning (KB) program is a government program that aims to control the rate of population growth. In Indonesia, the family planning program has been launched since 1970 and has shown significant results in reducing birth rates. However, there are still several obstacles in implementing the family planning program, one of which is the low participation rate of couples of childbearing age (PUS). Methods: This study used a cross-sectional design with 384 PUS as respondents. Data was collected through questionnaires and analyzed using logistic regression. Results: The results of the study showed that the factors that significantly influenced PUS' decision to take part in the family planning program in Purwakarta Regency were knowledge about family planning (OR = 2.89; 95% CI: 1.73-4.82), husband's support (OR = 2.15 ; 95% CI: 1.28-3.59), and access to family planning services (OR = 1.83; 95% CI: 1.10-3.05). Conclusion: Factors that significantly influence PUS's decision to participate in the family planning program in Purwakarta Regency are knowledge about family planning, husband's support, and access to family planning services.